A Damaged Medium Model for Describing Dynamic Spallation Fracture. (2017) - Volkov, I.A.; Vorobtsov, I.V.; Igumnov, L.A.; Markov, I.P.; Litvinchuk, S.Yu.
Abstract: The main physical laws of the failure process in structural materials under dynamic loading modes and mathematical models of such processes are considered. To describe dynamic spallation fracture, a version of governing equations of damaged medium mechanics is developed, consisting of three interrelated parts: governing equations describing plastic behavior of the material as a function of the failure process, evolution equations of damage accumulation, and a strength criterion of the damaged material. A methodology for determining material parameters of kinetic equations of damage accumulation, based on minimizing the quadratic deviation between theoretical and experimental data is used. Comparison of the obtained computational results with the experimental data on dynamic spallation fracture in plates during plane impact shows that the present model of damaged medium mechanics adequately describes experimental data and can be effectively used in analyzing dynamic spallation fracture.